Navigating circular economy and digitalisation: a comparative study of manufacturing strategies in the UK and Saudi Arabia - Sarfraz, Shoaib; Sherif, Ziyad; Alshammari, Serhan; Salonitis, Konstantinos (Elsevier, 2024)
This study presents an integrated framework for evaluating manufacturing maturity in embracing circular economy principles and digital technologies, with a focus on comparing best practices between the UK and Saudi Arabia. The framework incorporates circular economy principles, such as waste elimination, material circulation, and nature regeneration, across product, process, and business model innovations. It also encompasses key Industry 4.0 technologies that facilitate smart and connected manufacturing. Utilising secondary data sources, the research maps the capabilities of selected manufacturers in both countries across categories including operations and technology. The findings indicate that the UK leads in most areas due to its sustained emphasis on sustainability and digitalisation over the past decade. In contrast, Saudi Arabia exhibits a lack of concrete policies and investments in these domains but demonstrates the potential for adapting UK practices to its unique context. The study proposes a staged roadmap to guide Saudi Arabia in a systematic transition towards circular and digital manufacturing, emphasising coordinated efforts in policy, infrastructure development, skills enhancement, and industry collaboration. This comparative assessment offers valuable insights into manufacturing best practices and opportunities for improvement.
57th CIRP Conference on Manufacturing Systems 2024 (CMS 2024), 29th to 31st May 2024, Póvoa de Varzim, Portugal
Keywords: Circular Economy; Digital Transformation; Industry 4.0; Benchmarking; Saudia Arabia; UK